1997
DOI: 10.4038/jnsfsr.v25i3.5030
|View full text |Cite
|
Sign up to set email alerts
|

Change in growth and yield characteristics of Musa cv Mysore ("Embul" banana) with increasing age of the crop

Abstract: Banana (Musa spp.) is a major semi-perennial fruit crop in Sri Lanka. A study was conducted at the Ftegional Agricultural Research and Development Centre, Angunakolapelessa to investigate the effect of age on growth and yield of banana cv Mysore ("Embul", AAB group). Thirty-seven "Embul" banana accessions collected from various ecological regions of Sri Lanka were studied in a Randomized Complete Block Design with three replicates. The observations were recorded in three consecutive years. Number of leaves per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Aside from climatic variables, other factors may have affected plantain productivity, such as plot age. Field experiments with bananas have reported both positive (Sirisena and Senanayake, 1997) and negative (Smale and Tushemereirwe, 2007) effects of age on yield. In light of this, it is possible that the decline in plantain productivity observed in Cameroon was due to crop senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from climatic variables, other factors may have affected plantain productivity, such as plot age. Field experiments with bananas have reported both positive (Sirisena and Senanayake, 1997) and negative (Smale and Tushemereirwe, 2007) effects of age on yield. In light of this, it is possible that the decline in plantain productivity observed in Cameroon was due to crop senescence.…”
Section: Discussionmentioning
confidence: 99%
“…1 Bast fiber was one of the common textile materials in the market used by mankind for thousands of years. 2 Sirisena and Senanayake 3 reported that banana (Musa acuminate) is the most widely cultivated fruit crop in Sri Lanka. There are about 27-28 cultivars grown in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Sirisena and Senanayake 3 reported that banana ( Musa acuminate ) is the most widely cultivated fruit crop in Sri Lanka. There are about 27–28 cultivars grown in the country.…”
Section: Introductionmentioning
confidence: 99%